Primary Persistent Atrial Fibrillation: A Distinct Arrhythmia Subentity of an Ablation Population. (12th October 2015) - KONRAD, TORSTEN; THEIS, CATHRIN; MOLLNAU, HANKE; SONNENSCHEIN, SEBASTIAN; OCETE, BLANCA QUESADA; BOCK, KARSTEN; MÜNZEL, THOMAS; ROSTOCK, THOMAS
Primary Persistent AF: Introduction: Persistent atrial fibrillation (persAF) can occur either as a sustained arrhythmia that has progressed from initially paroxysmal AF or as primary persAF without a history of any spontaneously terminated episode. There is a paucity of data differentiating between the 2 different persAF entities. Thus, we prospectively evaluated baseline characteristics, electrophysiological features, and ablation outcome in these 2 patient cohorts. Methods and results: A total number of 154 consecutive persAF patients (63 ± 10 years, f = 42, longstanding persAF = 60) were characterized in terms of having primary persAF (P‐persAF group) or persAF that secondarily progressed from paroxysmal AF (S‐persAF group). All patients underwent de novo catheter ablation using the stepwise approach. PersAF entities were characterized by detailed patient history, sequential Holter monitoring, and reports of documented modes of AF conversion, respectively. The P‐persAF group had a higher number of young patients (<50 years), a shorter AF history, and a higher number of congestive heart failure. The HATCH score did not differ between the groups. Procedural AF termination rate was significantly higher in S‐persAF than in P‐persAF patients (n = 55 [81%] vs. n = 58 [68%], P = 0.043). At 1‐year follow‐up, the arrhythmia‐free survival after a single procedure was significantly lower in patients with P‐persAF (26% vs. 43%, P = 0.016). Categorization to P‐persAF was the strongest independent predictor of arrhythmia recurrence. Conclusions: P‐persAF seems to be a specific arrhythmia entity that is associated with a lower AF‐termination rate and a worse outcome after catheter ablation as compared to S‐persAF.